(untitled) (jornal of the libyan geographical society, 2009)
The defining characteristic of internal migration patterns in western Libya is that it is an urban-oriented movement, specifically towards Tripoli, the country’s largest urban center and the only urban area in the region. The phenomenon of rural-to-urban migration is not new in North Africa, but it intensified in the 20th century. As a result of the economic expansion of coastal cities, the northern coast traditionally attracted Libyan migrants. The motivation for Libyan migrants was mostly the favorable natural conditions for agriculture on the coast of Tripoli or mining in the oil fields of Sirte, as well as living in urban centers.